PENGARUH BAURAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN MOBIL TOYOTA AVANZA PADA AUTO 2000 CABANG PALEMBANG - Daniel Mynhart; Zakaria Wahab; Islahudin Daud; A Widad (UNIB Press, 2019)
The purpose of this study is to determine the effect of the promotion mix on the purchasedecision of Toyota Avanza cars at AUTO 2000 Palembang Branch. Data in this study werecollected through distributing questionnaires to respondents. The number of samples used inthis study were 100 respondents. The technique used in this study sample was purposivesampling. The results of the analysis in this study indicate simultaneously (F test) theindependent variables, namely personal sales, sales promotion, advertising and publicrelations significantly influence the dependent variable, namely the purchase decision of theToyota Avanza at AUTO 2000 Palembang Branch. Partially (t test), the variables of personalsales, sales promotion and advertising have a significant effect on purchasing decisions. Asfor the public relations variable does not significantly influence the purchase decision. Themost dominant variable influencing purchase decisions is the advertising variable.